The suitability of some blood gas and biochemical parameters as diagnostic tools or early indicators of ascites syndrome in broiler sire lines. Issue 3 (26th November 2015) - Hasanpur, K.; Nassiri, M. R.; Hosseini Salekdeh, G.; Vaez Torshizi, R.; Pakdel, A.; Kermanshahi, H.; Naghous, M.
Summary: In recent few years, there have been some attempts to find a reliable indicator trait as a selection criterion against susceptibility to ascites syndrome (AS). Blood parameters were of great interest as they could be measured in live animals without implementing an ascites‐inducing challenge (AIC). In this work, the suitability of some blood parameters was evaluated for diagnosing AS‐susceptible chicks in later steps of the disease in trial 1 as well as their early predictive ability in trial 2. In the first trial, one hundred 1‐day‐old chicks from two pure broiler lines namely S1 and S2 and, in the second trial, 226 1‐day‐old chicks from line S2 were subjected to AIC. Saline drinking water (1200 mg/l) and lower‐than‐standard ambient temperatures were the implemented AICs in trials 1 and 2 respectively. The blood parameters including pH, partial pressure of O2 (pO2 ), partial pressure of CO2 (pCO2 ), bicarbonate ion concentration (BIC), percentage of haematocrit (HCT) and saturated haemoglobin (SaO2 ) were measured twice per each bird at days 28 and 35 in trial 1 and once in trial 2 at day 21. The results of the first trial revealed that in line S2 some of the blood parameters differed significantly between the ascitic and non‐ascitic groups following exposure to AIC. In this line, the incidence of AS was accompanied by a lower pO2, SaO2 and BIC, while with higher pCO2 and HCT values. In the second trial, however, although almost all of the parameters showed meaningful differences between the ascitic and non‐ascitic broilers, only mean difference of BIC parameter was statistically significant. The general conclusion of this study is that the blood parameters can somewhat have diagnostic ability in the condition in which the AIC is already present, whereas the results did not approve their usefulness as early predictors of AS.